The BRG1 Chromatin Remodeler Regulates Widespread Changes in Gene Expression and Cell Proliferation During B Cell Activation. Issue 1 (23rd September 2013) - Holley, Darcy W.; Groh, Beezly S.; Wozniak, Glenn; Donohoe, Dallas R.; Sun, Wei; Godfrey, Virginia; Bultman, Scott J.
Abstract Widespread changes in gene expression underlie B cell development and activation, yet our knowledge of which chromatin‐remodeling factors are essential is limited. Here, we demonstrate that the BRG1 catalytic subunit of SWI/SNF complexes was dispensable for murine B cell development but played an important, albeit selective, role during activation. Although BRG1 was dispensable for CD69 induction and differentiation into plasma cells based on the ability of mutant B cells to undergo hypertrophy and secrete IgM antibodies, it was required for robust cell proliferation in response to activation. Accordingly, BRG1 was required for only ∼100 genes to be expressed at normal levels in naïve B cells but >1, 000 genes during their activation. BRG1 upregulated fivefold more genes than it downregulated, and the toll‐like receptor pathway and JAK/STAT cytokine‐signaling pathways were particularly dependent on BRG1. The importance of BRG1 in B cell activation was underscored by the occurrence of opportunistic Pasteurella infections in conditionally mutant mice. B cell activation has long served as a model of inducible gene expression, and the results presented here identify BRG1 as a chromatin‐remodeling factor that upregulates the transcriptome of B cells during their activation to promote rapid cell proliferation and to mount an effective immune response. J. Cell. Physiol. 229: 44–52, 2014. © 2013 Wiley Periodicals, Inc.